Desenvolvimento de proteína quimérica e análise de seu potencial vacinal contra infecção experimental por Trypanosoma cruzi - Julia Teixeira de Castro (2020)
Chagas’ disease (CD), caused by the protozoan Trypanosoma cruzi (T. cruzi) accounts for ~10,000 deaths each year, mostly chronic patients. The available treatments have several adverse effects and present low efficacy during the chronic phase of disease. Therefore, the development of a prophylactic and therapeutic vaccine for CD is extremely important. Studies have shown the protective effect of Trans-Sialidase (TS) and Amastigote Surface Protein–2 (ASP-2) as vaccine antigens. In this work, a chimeric protein, named DTT-1, containing predicted HLA (Human Leucocyte Antigen)-ABC binding epitopes of both proteins was developed. In order to assess the potential of DTT-1 as a vaccine, C57BL/6 mice were immunized with three doses containing 10 ug of DTT-1 associated with two different adjuvants: CpG + Alum or Poly (I:C). For comparison, there were also groups vaccinated with the TS or the ASP-2 regions contained in DTT-1 (rTS and r-ASP-2). Thirty days post the last immunization, the animals were challenged with T. cruzi Y strain. The data showed that the vaccination with DTT-1 induced the secretion of IFN-γ and IL-10 by splenocytes after in vitro stimulation with rTS and rASP-2. It was also observed that DTT-1 was able to induce the production of antigen-specific total IgG, IgG1 and IgG2c. Moreover, this recombinant chimeric protein generated a significant response anti-T. cruzi, demonstrated by a decrease in parasitemia compared with control groups. In order to investigate whether the vaccination with DTT-1 would generate long-lasting immunity, mice were challenged with T. cruzi at 30, 90 or 180 days post immunization. DTT-1-immunized mice were found to develop low parasitemia levels up to 90 days, but showed an increase in parasite load with 180 days after immunization. The results obtained suggest that DTT-1 is a potential vaccine candidate against Chagas’ disease.